City in ruins : a novel [large type] - Winslow, Don, 1953- (Harper Large Print, an imprint of HarperCollins Publishers, 2024)
Danny Ryan is rich. Beyond his wildest dreams rich. The former dock worker, Irish mob soldier and fugitive from the law is now a respected businessman ; a Las Vegas casino mogul and billionaire silent partner in a group that owns two lavish hotels. Finally, Danny has it all: a beautiful house, a child he adores, a woman he might even fall in love with. Life is good. But then Danny reaches too far. When he tries to buy an old hotel on a prime piece of real estate with plans to build his dream resort, he triggers a war against Las Vegas power brokers, a powerful FBI agent bent on revenge and a rival casino owner with dark connections of his own. To save his life and everything he loves, Danny must become the ruthless fighter he once was--and never wanted to be again.--